The implication of chromosomal abnormalities in the surgical outcomes of Chinese pediatric patients with congenital heart disease - Yu, Xiafeng; Tao, Yu; Liu, Xu; Yu, Feng; Jiang, Chuan; Xiao, Yingying; Zhang, Haibo; He, Yongrui; Ye, Lincai; Wang, Ying; Zhou, Chunxia; Wang, Jian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Copy number variations (CNVs) have been shown to be overrepresented in children with congenital heart disease (CHD). Genetic evaluation of CHD is currently underperformed in China. We sought to determine the occurrence of CNVs in CNV regions with disease-causing potential among a large cohort of Chinese pediatric CHD patients and investigate whether these CNVs could be the important critical modifiers of surgical intervention. Methods CNVs screenings were performed in 1,762 Chinese children who underwent at least one cardiac surgery. CNV status at over 200 CNV locus with disease-causing potential was analyzed with a high-throughput ligation-dependent probe amplification (HLPA) assay. Results We found 378 out of 1,762 samples (21.45%) to have at least one CNV and 2.38% of them were carrying multiple CNVs. The detection rates of ppCNVs (pathogenic and likely pathogenic CNVs) were 9.19% (162/1,762), significantly higher than that of the healthy Han Chinese individuals from The Database of Genomic Variants archive (9.19% vs. 3.63%; P = 0.0012). CHD cases with ppCNVs had a significantly higher proportion of complex surgeries compared to CHD patients with no ppCNVs (62.35% vs. 37.63%, P < 0.001). Duration of cardiopulmonary bypass and aortic cross clamp procedures were significantly longer in CHD cases with ppCNVs (all P < 0.05), while no group differences were identified for complications of surgery and one-month mortality after surgery. The detection rate of ppCNVs in the atrioventricular septal defect (AVSD) subgroup was significantly higher than that in other subgroups (23.10% vs. 9.70%, P = 0.002). Conclusions CNV burden is an important contributor to Chinese children with CHD. Our study demonstrated the robustness and diagnostic efficiency of HLPA method in the genetic screening of CNVs in CHD patients.